Answer:
For [0,4] : -64
For [1,4] : -80
For [3.9,4] : -126.4
For [3.99,4] : -127.84
For [3.999,4] : -127.984
Explanation:
First we establish that we have the next function:
h(t) = -16t² + 256
Now, to find the average rate of change we have to define the change in the output of the function and the change in the input of the function:
Average rate of change = Change in the output / Change in the input
Which in this case will be represented by:
Average rate of change = h(t2) - h(t1) / t2 - t1
So now we resolve the function for each time interval and calculare the average rate of change:
For [0,4] :
h(0) = -16(0)² + 256 = 256
h(4) = -16(4)² + 256 = 0
Average rate of change = [0 - 256] / [4 - 0] = -64
For [1,4] :
h(1) = -16(1)² + 256 = 240
h(4) = -16(4)² + 256 = 0
Average rate of change = [0 - 240] / [4 - 1] = -80
For [3.9,4] :
h(3.9) = -16(3.9)² + 256 = 12.64
h(4) = -16(4)² + 256 = 0
Average rate of change = [0 - 12.64] / [4 - 3.9] = -126.4
For [3.99,4] :
h(3.99) = -16(3.99)² + 256 = 1.2784
h(4) = -16(4)² + 256 = 0
Average rate of change = [0 - 1.2784] / [4 - 3.99] = -127.84
For [3.999,4] :
h(3.999) = -16(3.999)² + 256 = 0.127984
h(4) = -16(4)² + 256 = 0
Average rate of change = [0 - 0.127984] / [4 - 3.999] = -127.984